Observations of Litter Deposited in the Deep Waters of Isla del Coco National Park, Eastern Tropical Pacific - Naranjo-Elizondo, Beatriz; Cortés, Jorge (Frontiers in Marine Science, 2018)
Marine debris is recognized as a major threat to biodiversity and can be found ubiquitously even in remote regions, including deep-sea environments. Isla del Coco National Park is known as one of the best protected areas around the world, a preferred diving destination, and is also renowned for large aggregations of pelagic species that attract illegal commercial fisheries. Despite its pristine reputation, this study demonstrates that anthropogenic debris can affect this remote and well protected area. Images of marine debris were taken using the DeepSee submersible, mainly plastic litter from fishing gear were found between 200 and 350 m depth. A total of 40 items of debris were found in 5.48% of 365 dives, 60% of the items were plastics, and local boat and fishing activities provided most of litter. Our aim with this research is to raise awareness about the potential problem of solid wastes and fishing gear deposited in the deep environments of Isla del Coco National Park and to explore the potential implications for the ecological integrity of this protected area, including ghost fishing and the possible ingestion of pollutants. These results provide useful management information for the area, especially if one considers the constant pressure of illegal fishing and tourism at Isla del Coco National Park.